Oral administration of hydroxylated-graphene quantum dots induces intestinal injury accompanying the loss of intestinal stem cells and proliferative progenitor cells. Issue 10 (26th November 2019) - Yu, Lan; Tian, Xin; Gao, Dexuan; Lang, Yue; Zhang, Xiang-Xiang; Yang, Chen; Gu, Meng-Meng; Shi, Jianming; Zhou, Ping-Kun; Shang, Zeng-Fu
Abstract: Graphene quantum dots (GQDs) have gained significant attention in various biomedical applications. The physicochemical properties of these nanoparticles, including toxic effects, are largely determined by their surface modifications. Previous studies have demonstrated high in vitro cytotoxicity of the hydroxylated GQDs (OH-GQDs). The focus of this study was on the intestinal toxicity of OH-GQDs. Briefly, C57BL/6J mice were given daily oral gavage of 0.05, 0.5 or 5 mg/kg OH-GQD for 7 days, and the indices of intestinal damage were evaluated. Higher doses of the OH-GQDs caused significant intestinal injuries, such as enhanced intestinal permeability, shortened villi and crypt loss. The number of Lgr5 + intestinal stem cells also decreased dramatically upon OH-GQDs exposure, which also inhibited the Ki67 + proliferative progenitor cells. In addition, an increased number of crypt cells harboring the oxidized DNA base 8-OHdG and γH2AX foci were also detected in the intestines of OH-GQD-treated mice. Mechanistically, the OH-GQDs up-regulated both total and phosphorylated p53. Consistent with this, the average number of TUNEL + and cleaved caspase-3 + apoptotic intestinal epithelial cells were significantly increased after OH-GQDs treatment. Finally, a 3-dimensional organoid culture was established using isolated crypts, and OH-GQDs treatment significantly reduced the size of the surviving intestinal organoids. Taken together, the intestinal toxicity of the OH-GQDs should be taken into account during biomedical applications.